Pathophysiology of Idiopathic Atrial Fibrillation - Prognostic and Treatment Implications - Weijs, B.; Schotten, U.; Crijns, H.J.G.M. (Current Pharmaceutical Design, 2015)
The term idiopathic or lone atrial fibrillation (AF) is commonly used in the young and apparently healthy individual who suffers from AF. Although there is conflicting evidence concerning prognosis, these patients are at risk to develop (vascular) comorbidities in the years following AF onset. It is conceivable that early stages of vascular disease, undetectable by the routine diagnostics, may contribute to the pathophysiology of “apparently” idiopathic AF. At present, more advanced diagnostics have become available that can be deployed at low threshold in order to detect early stage or yet subclinical cardiovascular disease. In this respect one could raise the question whether idiopathic AF exists at all or that the arrhythmia acts as a harbinger of as yet undetected underlying vascular disease in this specific population. Assuming that idiopathic AF is the final arrhythmic expression of underlying genetic mutations and/or vascular diseases, high priority should be given to trace identifiable predisposing factors or the presence of early stages of underlying disease in order to treat these, or prevent their complications. A more comprehensive quest for potential hidden causes of idiopathic AF creates new therapeutic dilemmas, but also encourages further research regarding pathophysiology and new early treatment opportunities in patients with atrial fibrillation in general. The present review provides more insight regarding diverse pathophysiological mechanisms in the fundamental basis for idiopathic AF, outlines prognostic and treatment implications, and questions the robustness of its definition.
Keywords: pathophysiology